2019
DOI: 10.1080/14737167.2019.1703182
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavior therapy for health anxiety: systematic review and meta-analysis of clinical efficacy and health economic outcomes

Abstract: Introduction: Health anxiety, also known as 'hypochondriasis', is a common, distressing and costly condition that responds to cognitive behavior therapy (CBT) but evidence pertaining to response and remission rates, treatment in routine care, therapist-guided Internet-delivered CBT (ICBT) and health economics has not been systematically reviewed. Areas covered: In this systematic review and meta-analysis we searched PubMed, PsycINFO, and OATD (17/06/2019) for randomized controlled trials (RCTs) comparing CBT t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 68 publications
2
34
1
1
Order By: Relevance
“…There is some evidence on the cost-effectiveness of eHealth interventions for depression and anxiety in primary care settings when compared to care as usual and waiting list control conditions [51] as well as for a range of mental disorders when compared to conventional CBT [112,113]. However, as only a few systematic reviews have systematically investigated the cost-effectiveness of digital interventions to date, these findings should be interpreted with caution.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…There is some evidence on the cost-effectiveness of eHealth interventions for depression and anxiety in primary care settings when compared to care as usual and waiting list control conditions [51] as well as for a range of mental disorders when compared to conventional CBT [112,113]. However, as only a few systematic reviews have systematically investigated the cost-effectiveness of digital interventions to date, these findings should be interpreted with caution.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…Severe health anxiety (SHA) is especially expected to increase, due to its association with COVID‐19‐related anxieties and public health measures (Asmundson & Taylor, 2020; Jungmann & Witthöft, 2020). Cognitive–behavioural therapy (CBT) is a well‐evidenced frontline treatment for SHA, which is evidenced as effective both face‐to‐face and remotely (Axelsson & Hedman‐Lagerlöf, 2019; Cooper, Gregory, Walker, Lambe, & Salkovskis, 2017). This includes evidence of the clinical‐ and cost‐effectiveness of remote‐CBT (rCBT) for SHA delivered over video conferencing (Morriss et al, 2019).…”
Section: Predicting Outcomes and Sudden Gains From Initial In‐session Interactions During Remote Cognitive–behavioural Therapy For Severementioning
confidence: 99%
“…It is estimated that 3.4% of the total population and 20% of patients referred to health clinics suffer from HA (2,3). Persistent and excessive fear or extreme anxiety about the disease not only leads to suffering and dysfunction, but also causes a significant increase in health and social costs (4). It has been found that the cost of healthcare for HA patients referring to physicians is 41%-78% higher than patients who refer to physicians with a specific disease (4), which indicates the HA-related financial burden imposed on the individual and society.…”
Section: Introductionmentioning
confidence: 99%